A violência doméstica no seio da relação conjugal e a sua relação com o estatuto da mulher na sociedade - Gavião, Isabel Harriet Gourgel (2015)
Domestic violence is one of the most serious problems that contemporary society faces. Domestic violence that specifically occurs between spouses is a particular case of domestic violence that has caused a high number of victims - mostly women - putting thus an enormous challenge to states with regard to combating this problem. In this thesis we intend to proceed with the study of this phenomenon in the Angolan context. The objective of this study is trying to understand how such violence is manifested in Angola, what factors may be at it’s source and what effects can be observed on the victims, their families and in society itself. Being the Angolan people strongly linked to traditions and customs, it seemed interesting to also address the issue of domestic violence under customary law. In addition to the problem of the study itself, we proceed to exposure and analysis of how the state and civil society have intervened in this matter. At the end of this study, we conclude that despite the fact that the issue of domestic violence has received more attention in recent years from the public entities and society in general, there is still a long way to go. This path involves not only more actions of the state but also a change of mentality, which can enable the break with social stereotypes in adopting a different behavior over the issue under review and internalizing that human dignity is the basic principle of any state that proclaims democratic rights.